A systemic review on chemotherapy induced nausea and vomiting- risk and clinical management with alternative therapies - Derangula Lavanya; VelugotlaPranathi Prasanna; Asma Firdous; Sneha Thakur (Cancer Treatment and Research Communications)
Chemotherapy-induced nausea and vomiting (CINV) affects up to 80 % of cancer patients, significantly impacts the health in terms of their quality of life and straining healthcare resources. CINV is categorized into anticipatory, acute, and delayed types. Risk factors include younger age, female sex, a history of CINV, and the emetogenic potential of the chemotherapy agents. Drugs like cisplatin and anthracycline-cyclophosphamide combinations are highly emetogenic and pose the greatest risk. Advances in managing CINV include evidence-based guidelines and the use of antiemetic medications such as 5-HT3 receptor antagonists, NK-1 receptor antagonists, and corticosteroids. These measures have reduced vomiting incidents, but complete control of nausea remains challenging. Up to 60 % of patients still experience delayed nausea, and anticipatory nausea and vomiting affect up to 30 % and 20 % of patients, respectively, by the fourth treatment cycle. Clinical and alternative therapies are though effective, research suggests integrated management for CINV. Tailored approach is needed as it has both psychological and physiological influence. To overcome the challenges, the guidelines and antiemetic regimens should be improved according to individual patient evaluation and awareness is necessary. Research is ongoing to develop targeted therapies that combine pharmacological and behavioral interventions to improve CINV management, especially for patients who do not respond well to current antiemetic treatments.